Lacunary statistical boundedness of order ? for sequences of fuzzy numbers - Altinok, Hifsi; Et, Mikail; Altin, Yavuz (Ios Press, 2018)
In the present paper, we introduce the concept of lacunary statistical boundedness of order beta for sequences of fuzzy numbers and give some relations between lacunary statistical boundedness of order beta and statistical boundedness.
Keywords: Quotient Space; Convergence; Hemirings